Visualizing Execution Histories on Multiple Memory Consistency Models - Melo, Alba Cristina Magalhães de; Chagas, Simone Cintra (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1998)
In order to provide a better understanding on the semantics of the memory models, many researchers have proposed formalisms to define them. Unfortunately, many of the formal definitions are so complex that it is still difficult to say what kind of execution history can be produced on a particular memory consistency model. In this paper, we propose a visualization tool that shows what operations orderings could lead to user-defined execution histories on different memory consistency models. The memory consistency model defines order relations that restrict the executions that can be produced. We also present a prototype of this visualization tool that analyses two-processor execution histories for two memory consistency models: sequential consistency and PRAM consistency.